Distribution of Secanting Rice to Underprivileged Families in Bintan Regency - Saputra, Haidir; Darmawan, Ikhsan; Suryaningsih, Suryaningsih (Asian Journal of Community Services, 2025)
Poverty, being a major problem in Bintan Regency, hampers people's access to their basic food needs. The purpose of the "Distribution of Secanting Rice to Underprivileged Families" program is to help underprivileged families overcome their difficulties in life by providing rice. This community service aims to find out how the mechanism for distributing secanting rice assistance to underprivileged families works. This program involves various elements of society, from funding, fundraising, or donations, to providing direct assistance to target families. The results of community service related to the implementation of this program show an increase in household food security and greater social concern among the Bintan community. This program is expected to be a long-term solution to the food problems of poor families.